The influences of gender, courses and speaking English at home on factors contributing to poor spoken English / Cheang Eng Kwong - Cheang, Eng Kwong (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2009)
This paper highlights the factors that contribute to the poor proficiency of spoken English among the 196 diploma students from Engineering and Hotel Faculties at UiTM Penang. The objectives are to examine the problems faced by the students with regard to their spoken English on campus and to compare the different factors influenced by gender, courses and speaking English at home. Chi-square test and reliability test were conducted to measure the significant relationship and reliable consistency. Both tests were found to be significantly related and consistent. The results of the study also conclude that both internal and external factors have resulted in the poor use of spoken English among the students.